Mortality of Mute Swan progeny in an area of south Staffordshire - Coleman, A E; Minton, C D T (Wildfowl, 1980)
Mortality of Mute Swan Cygnus olor progeny has been studied since 1961 in a 550 square mile (1,440 sq km) area of south Staffordshire. Nearly half of all clutches were stolen by humans man’s interference being the major cause of mortality before hatching. Rearing success was high, approximately 50% of the broods fledged without loss. The highest mortality after fledging occurred during the first year of life with peak periods in both October and March. Overhead wires were the commonest cause of known death. Birds in their second and later years show mortality peaks between January and April.